2011
DOI: 10.1007/s11814-010-0472-4
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of ammonia-based wet flue gas desulfurization in the spray scrubber

Abstract: A mathematical model of ammonia-based wet flue gas desulfurization process was developed based on the double film theory. The calculated results of the desulfurization system for two 220 t·h −1 boilers per unit by this model were compared to that of corresponding measured data. It was found that the calculated results agree well with the measured data for the operating conditions of pH, liquid/gas ratio and SO 2 concentration. This model can provide predictions of the absorption performance of an ammonia-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Gao et al [4] performed experiments in a stirred tank reactor to investigate the characteristics of the reaction between ammonium sulfite, the main desulfurizing solution and the flue-gas-contained sulfur dioxide during the process of ammonia-based WFGD in a power plant, and the experimental results indicated that the reaction was controlled concurrently by gas-and liquid-film. Jia et al [9,10] developed a mathematical model according to the double film theory to study the desulfurization process of ammonia-based WFGD in the spray scrubber, and the calculated results for two 220 t h À1 boilers unit in China by this model agreed well with the measured data. This model could provide predictions of the absorption performance and appeared to be helpful for designing scrubbers for SO 2 absorption with ammonia absorbent.…”
Section: Introductionmentioning
confidence: 73%
“…Gao et al [4] performed experiments in a stirred tank reactor to investigate the characteristics of the reaction between ammonium sulfite, the main desulfurizing solution and the flue-gas-contained sulfur dioxide during the process of ammonia-based WFGD in a power plant, and the experimental results indicated that the reaction was controlled concurrently by gas-and liquid-film. Jia et al [9,10] developed a mathematical model according to the double film theory to study the desulfurization process of ammonia-based WFGD in the spray scrubber, and the calculated results for two 220 t h À1 boilers unit in China by this model agreed well with the measured data. This model could provide predictions of the absorption performance and appeared to be helpful for designing scrubbers for SO 2 absorption with ammonia absorbent.…”
Section: Introductionmentioning
confidence: 73%
“…The mass transfer and chemical reaction process of wet ammonia desulfurization process are complex and there are few studies on the prediction of wet ammonia desulfurization efficiency. Jia et al have developed a mathematical model to simulate the absorption of SO 2 in a spray scrubber [13]. Liu et al established a mathematical model of ammonia desulfurization in spray tower by analyzing the mass transfer rate equation of SO 2 in the process of ammonia desulfurization, and the experimental data agreed with the calculated values well [14].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies on SO 2 removal and abatement processes have been carried out to seek cost‐effective solutions for this issue , , , . Among the various methods employed in the abatement of SO 2 gas, dry flue gas desulfurization (FGD) technologies are thought to effectively solve those issues.…”
Section: Introductionmentioning
confidence: 99%